A survey of mange mite infestation in goats from Serdang, Malaysia - Sheikh Omar, Abdul Rahman; Saad, Mohd Zamri; Lee, C. C. (Universiti Pertanian Malaysia, 1984)

(untitled)
Forty goats submitted for necropsy to Universiti Pertanian Malaysia were studied for lesions caused by mange mites and for the presence of Illites. Twenty-eigh t goats had lesions, 24 (83%) in the adults showing both generalised and focal distribution and 4 (36%) in the kids, all focally distributed. Half of tile focally distributed lesions, were mild while the majority (83%) of the generalised lesions were severe. Four different species, Sarcoptes scabiei, Chorioptes bovis, Psoroptes sp, and Dcm odex caprae, were isolated from 18 goats. Three goats had mixed infestation